A Preliminary Report: The Hippocampus and Surrounding Temporal Cortex of Patients With Schizophrenia Have Impaired Blood-Brain Barrier - Goldwaser, Eric L.; Swanson, Randel L.; Arroyo, Edgardo J.; Venkataraman, Venkat; Kosciuk, Mary C.; Nagele, Robert G.; Hong, L. Elliot; Acharya, Nimish K. (Frontiers in Human Neuroscience, 2022)
Though hippocampal volume reduction is a pathological hallmark of schizophrenia, the molecular pathway(s) responsible for this degeneration remains unknown. Recent reports have suggested the potential role of impaired blood-brain barrier (BBB) function in schizophrenia pathogenesis. However, direct evidence demonstrating an impaired BBB function is missing. In this preliminary study, we used immunohistochemistry and serum immunoglobulin G (IgG) antibodies to investigate the state of BBB function in formalin-fixed postmortem samples from the hippocampus and surrounding temporal cortex of schizophrenia patients with schizophrenia (n=25) and non-schizophrenia controls without schizophrenia (n=27) matched for age, sex, and race. Since a functional BBB prevents the extravasation of IgGs, detection of IgGs in the parenchyma is used as direct evidence of BBB breakdown. We also developed a semi-quantitative approach to quantify the extent of IgG leak and therein BBB breach. Analysis of our immunohistochemistry data demonstrated a significantly higher incidence of IgG leak in schizophrenia patients with schizophrenia compared to controls. Further, BBB permeability was significantly higher in advanced-age patients with schizophrenia patients than both advanced-age controls and middle-aged schizophrenia patients with schizophrenia. Male patients with schizophrenia patients also demonstrated increased IgG permeability compared to control males. Interestingly, the extravasated IgGs also demonstrated selective immunoreactivity for neurons. Based on these observations, we suggest that BBB dysfunction and IgG autoantibodies could be two key missing pathoetiological links underwriting schizophrenia hippocampal damage.